1993
DOI: 10.1163/26660644-06301001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization, cytogenetic analysis, and geographical distribution of the Pygmy Marbled Newt Triturus marmoratus pygmaeus (Wolterstorff, 1905) (Caudata: Salamandridae)

Abstract: Triturus marmoratus pygmaeus, a problematicsubspecies of the Marbled Newt from the southern part of the Iberian Peninsula, is redescribed using specimens collected in the “typical” area. Diagnostic external morphological features are provided to permit the accurate determination of the specimens belonging either to T. m. marmoratus or to T. m. pygmaeus. These diagnostic features were applied to individuals both from the field and from museum collections. The results indicate a larger distributional area for to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…In species with a wide geographic distribution of the samples (e.g. T. marmoratus), the standard deviation is higher than for samples from a single locality, perhaps re ecting geographic variation, as the populations belong probably to different subspecies: T. marmoratus pygmaeus from Algarve (Portugal) and T. marmoratus marmoratus from El Berrueco (Madrid, Spain) (García-París et al, 1993;Barbadillo et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In species with a wide geographic distribution of the samples (e.g. T. marmoratus), the standard deviation is higher than for samples from a single locality, perhaps re ecting geographic variation, as the populations belong probably to different subspecies: T. marmoratus pygmaeus from Algarve (Portugal) and T. marmoratus marmoratus from El Berrueco (Madrid, Spain) (García-París et al, 1993;Barbadillo et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Triturus marmoratus and T. pygmaeus are similar, yet morphologically diagnosable species (García-París et al, 1993;Arntzen, 2018). They are genetically distinct (Espregueira Themudo and Arntzen, 2007b;Wielstra et al, 2019), with genetic admixture reported over several sections of their parapatric species border (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Adult and juvenile newts were caught by dip netting across Europe and Asiatic Turkey. Individuals were identifi ed to species based on morphology (García-París et al, 1993;Arntzen and Wallis, 1999). For phylogeny reconstruction, two to four populations per species were selected from a larger sample set, such that 1) identifi cations are in line with documented geographical distributions, 2) spatial coverage is large, and 3) samples from putative admixture zones are preferably excluded (Fig.…”
Section: Sampling Strategymentioning
confidence: 99%